1997
DOI: 10.2307/3237377
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and mechanical defense against herbivory in two sympatric species of desert Acacia

Abstract: Most African Acacia trees occur in semi-arid savannas, but some species grow in deserts at the periphery of their range in northern Africa and the Middle East. We studied Acacia raddiana and A. tortilis in the southern Negev desert of Israel. According to the resource availability hypothesis, plants in poor habitats invest heavily into anti-herbivore defense because losses to browsers are costly when growth rates are low. Few plants invest simultaneously in different categories of defense. This suggests that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 40 publications
7
95
2
Order By: Relevance
“…These results were considerably higher than the levels of 0)007}0)025% found in Ruschia spinosa (Stock et al, 1993), and quite similar to those described for Acacia tortilis (1)45}2)01%), A. nilotica (2)43}2)51%) (Brooks & Owen-Smith, 1994) or A. tortilis (2)14}2)49%) and A. raddiana (2)47}3)10%) (Rohner & Ward, 1997), typical species of semi-arid savanna. In the temperate zone, concentrations of protein-precipitating tannins varied from low levels of less than 0)5% (Ceanothus sp., Sorghum vulgare), and intermediate levels of 1)0}2)4% (Quercus sp., Cornus stolonifera) to high concentrations such as 5)2% measured in flowers of Epilobium angustifolium (Hagerman, 1987).…”
Section: Defensive Strategies Of Plantscontrasting
confidence: 38%
“…These results were considerably higher than the levels of 0)007}0)025% found in Ruschia spinosa (Stock et al, 1993), and quite similar to those described for Acacia tortilis (1)45}2)01%), A. nilotica (2)43}2)51%) (Brooks & Owen-Smith, 1994) or A. tortilis (2)14}2)49%) and A. raddiana (2)47}3)10%) (Rohner & Ward, 1997), typical species of semi-arid savanna. In the temperate zone, concentrations of protein-precipitating tannins varied from low levels of less than 0)5% (Ceanothus sp., Sorghum vulgare), and intermediate levels of 1)0}2)4% (Quercus sp., Cornus stolonifera) to high concentrations such as 5)2% measured in flowers of Epilobium angustifolium (Hagerman, 1987).…”
Section: Defensive Strategies Of Plantscontrasting
confidence: 38%
“…J. Kirk ex J. Léonard) regrowth with the greatest CT concentration (1.1 mg/g) of all defoliation treatments, while severe herbivory (75% and 100% defoliation) had no effect on CT concentration. In another study, Rohner and Ward (1997) reported light defoliation, 12 herbivores/km 2 , had no effect on CT concentration of twisted acacia (Acacia raddiana Savi), while heavier defoliation, 26 herbivores/ km 2 , increased CT concentration. Defoliating 75% of leaves had no effect on mopane CT concentration (Kohi et al 2009) but decreased CT concentration in smooth casearia (Casearia nitida (L.) Jacq.…”
Section: Introductionmentioning
confidence: 95%
“…CTs are hypothesized to be a plant defense against herbivory, and as such, herbivory intensity is thought to play a role in inducing CT concentration changes (Rohner & Ward 1997;Boege 2005;Kohi et al 2009). Kohi et al (2009) reported that intermediate herbivory pressure (50% defoliation) yielded mopane (Colophospermum mopane (J. Kirk ex Benth.)…”
Section: Introductionmentioning
confidence: 99%
“…Milewski et al (1991) reported branches of African Acacia trees that had been browsed by large herbivores as producing longer thorns and a greater density of thorns than inaccessible branches on the same trees. Rohner & Ward (1997) also reported intense herbivory of Acacia tortilis as increasing thorn length and density. Long thorns deter large herbivores by decreasing bite sizes and biting rates (Cooper & Owen-Smith, 1986;Belovsky et al, 1991;Gowda, 1996).…”
Section: Woody Plant Response To Herbivorymentioning
confidence: 99%
“…Owen-Smith & Cooper (1987) reported fewer plants as investing in both chemical and structural anti-herbivore defences to reduce costs to growth and reproduction. Acacia tortilis is heavily defended by both chemical and structural defences (Rohner & Ward, 1997;Sebata et al, 2011). Most Acacia species occur in areas of low fertility (Rohner & Ward, 1997) and adapt to these conditions by slow growth rates and efficient use of available nutrients (Coley et al, 1985), which may explain the ability of A. tortilis to invest in both types of defence.…”
Section: Woody Plant Response To Herbivorymentioning
confidence: 99%